Discourse Strategies in Chief Olusegun Obasanjo’s Letter to President Goodluck Ebele Jonathan - Ojo, George Adekunle; Omotunde, Samuel Adebayo; Akintoye, Samuel Oluwole (European Scientific Journal, ESJ, 2022)
The paper sets out to investigate the discourse strategies deployed by former President Olusegun Obasanjo in his open letter to President Jonathan on December 12, 2013 which was published in most of the nation’s major newspapers. The work adopts M.A.K Halliday’s Systemic Functional Grammar as its theoretical framework because of the great importance which the model attaches to meanings and functions of a linguistic expression in relation to its context of usage. The researchers, through content and qualitative analysis, identify the discourse strategies used by the encoder of the speech to have the desired maximum effects on the decoders, especially President Goodluck Jonathan. Our findings reveal that President Obasanjo makes use of six discourse strategies in the letter for achieving some aims. The discourse strategies are: references to national interest; using the vocative “Mr President”; mentioning and portraying God in different perspectives; making direct appeals to the president; making references to late Gen. Sanni Abacha and copious repetitions of Nigeria and Nigerians in the text.